The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.12688/f1000research.10009.1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lectin-like transcript-1 in human tissues

Abstract: Background: Receptor-ligand pairs of C-type lectin-like proteins have been shown to play an important role in cross talk between lymphocytes, as well as in immune responses within concrete tissues and structures, such as the skin or the germinal centres. The CD161-Lectin-like Transcript 1 (LLT1) pair has gained particular attention in recent years, yet a detailed analysis of LLT1 distribution in human tissue is lacking. One reason for this is the limited availability and poor characterisation of anti-LLT1 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…However, some PB NK cells can express the CD161 antigen, also called NKRP1A (67, 68). This receptor is upregulated on NK cells upon stimulation with IL2 and, more importantly, it is expressed on majority of intestinal infiltrating lymphocytes (68, 69), including NK cells and some subsets of ILC (2, 5, 10). It has been demonstrated that CD161 can function as an adhesion molecule involved in the transmigration of PB CD4 + T cells through endothelial cells (70).…”
Section: Nk Cell Localization In the Gutmentioning
confidence: 99%
“…However, some PB NK cells can express the CD161 antigen, also called NKRP1A (67, 68). This receptor is upregulated on NK cells upon stimulation with IL2 and, more importantly, it is expressed on majority of intestinal infiltrating lymphocytes (68, 69), including NK cells and some subsets of ILC (2, 5, 10). It has been demonstrated that CD161 can function as an adhesion molecule involved in the transmigration of PB CD4 + T cells through endothelial cells (70).…”
Section: Nk Cell Localization In the Gutmentioning
confidence: 99%
“…Because LLT1 can be expressed on different cell and tissue types, it presents the possibility for the cancer cells to escape the immunosurveillance of NK cells [ 102 ]. We have shown that the expression of LLT1 on target tissues such as triple-negative breast cancer cells and prostate cancer cells inhibits the NK cell response ( Figure 2 ) [ 17 , 103 ].…”
Section: Nk Cell Receptorsmentioning
confidence: 99%
“…CD161 is expressed by the majority of SI PLZF + CD4 + T cells (Figure 1, D and F) and has been ascribed conflicting roles in either the activation or inhibition of human immune cells (45)(46)(47). LLT1, the natural ligand for CD161, is broadly distributed in human tissues, with the highest levels of expression in immune-privileged sites (48,49). LLT1 was expressed on the majority of intestinal CD14 + antigen-presenting cells (APCs), but not CD11c + CD14 -DCs ( Figure 7C).…”
Section: Introductionmentioning
confidence: 99%